Effects of diamond as a main carbon source on the fabrication and mechanical properties of reaction-bonded SiC - Park, Jun Hyung; Kim, Dong Jun; Kim, Seong Won; Youm, Mi Rae; Nahm, Sahn; Park, Sang Whan (Pergamon Press Ltd., 2024)
RBSC with a low residual Si less than 5 vol% was fabricated using SiC-C preform with diamond as a main carbon source by a conventional reaction sintering process at the temperature range between 1500 degrees C and 1800 degrees C. The diamond content in the SiC-C preform varied from 10 wt% to 17 wt%. The diamond as the main carbon source used in SiC-C preform effectively minimized the residual Si in RBSC by increasing the reaction of diamond due to the enhanced Si melt infiltration even in SiC-C preform with high carbon content. The Si melt infiltration should be performed above 1600 degrees C for the complete reaction of diamond particles with size of 0.5 mu m because of the relatively low dissolution rate of diamond in Si melt. The flexural strength of RBSC with residual Si content less than 7 vol% exceeded 400 MPa. The flexural strength of RBSC was increased with decreasing residual Si content, but sharply decreased by the residual carbon accompanying pores in RBSC. RBSC with low residual Si content displayed moderate flexural strengths around 200 MPa even above Si melt temperature because of the formation of continuous SiC structure in RBSC by the enhanced grain growth of SiC. Vickers hardness of RBSC was steadily increased from 17.7 GPa to 24.6 GPa with decreasing residual Si.